Novel PPARγ Modulator GED-0507-34 Levo Ameliorates Inflammation-driven Intestinal Fibrosis. Issue 2 (February 2016) - Speca, Silvia; Rousseaux, Christel; Dubuquoy, Caroline; Rieder, Florian; Vetuschi, Antonella; Sferra, Roberta; Giusti, Ilaria; Bertin, Benjamin; Dubuquoy, Laurent; Gaudio, Eugenio; Desreumaux, Pierre; Latella, Giovanni
Abstract : Background: Intestinal fibrosis is mainly associated with Crohn's disease and is defined as a progressive and excessive deposition of extracellular matrix components. No specific antifibrotic therapies are available. In this study, we evaluate the antifibrotic effect of a novel 5-ASA analog able to activate the peroxisome proliferator-activated receptor γ, named GED-0507-34 Levo. Methods: Colonic fibrosis was induced in 110 C57BL/6 mice by 3 cycles of 2.5% (wt/vol) dextran sulfate sodium administration for 6 weeks. The preventive effects of oral daily GED (30 mg·kg −1 ·d −1 ) administration were evaluated using a macroscopic and histological score and also through biological endpoints. Expression of main markers of myofibroblasts activation was determined in transforming growth factor (TGF-β)–stimulated intestinal fibroblasts and epithelial cells. Results: GED improved macroscopic and microscopic intestinal lesions in dextran sulfate sodium-treated animals and reduced the profibrotic gene expression of Acta2, COL1a1, and Fn1 by 1.48-folds ( P < 0.05), 1.93-folds ( P < 0.005), and 1.03-fold ( P < 0.05), respectively. It reduced protein levels of main markers of fibrosis (α-SMA and Collagen I-II) and the main TGF-β/Smad pathway components. GED also decreased the interleukin-13 and connective tissue growth factor expression by 1.89-folds ( P < 0.05) and 2.2-folds ( P < 0.005), respectively. GED inhibited TGF-β–induced activation of both fibroblast and intestinal epithelial cell lines, by regulating mRNA expression of α-SMA and fibronectin, and restoring the TGF-β–induced loss of intestinal epithelial cell markers. GED treatment also reduced the TGF-β and ACTA1 expression in primary human intestinal fibroblasts from ulcerative colitis patients. Conclusions: GED ameliorates intestinal fibrosis in dextran sulfate sodium-induced chronic colitis in mice and regulates major profibrotic cellular and molecular mechanisms. Abstract : Article first published online 30 October 2015.